Do You Second That Emotion? An Empirical Study on the Emotional Impact of Subtitling on the Subtitler - Georgiou, Nadia; Perdikaki, Katerina (Journal of Audiovisual Translation, 2020)
This paper discusses the emotions experienced by subtitlers who subtitle sensitive audiovisual material. “Sensitive audiovisual material” refers to audiovisual texts which deal with controversial and emotive topics, such as abuse, war, torture. This topic has remained under-researched in subtitling, despite having been sporadically explored in other fields of translation (Hubscher-Davidson, 2017; Rojo and Ramos Caro, 2016; Tabakowska, 2016). The data presented in this paper expand upon and complement the findings discussed in Perdikaki and Georgiou (2020) based on an online survey completed by 170 subtitlers. For the current paper, the data discussed come from an online focus group with three professional subtitlers and face-to-face interviews with one freelance subtitler as well as a team interview with two in-house quality control editors. Having confirmed in our previous study that many subtitlers are affected by the sensitive AV material they subtitle, this paper aims at a more nuanced exploration of how subtitlers regulate emotions elicited on-the-job, offering specific examples as well as emotion management techniques. Finally, the perspective of emotional responsiveness, depending on socio-economic contexts as well as the linguistic arsenal of the subtitler, is briefly discussed.